Comparison of various aircraft routing strategies using the air traffic simulation model airtraf 2.0 - Yamashita, H. (author); Yin, F. (author); Grewe, V. (author); Jockel, P. (author); Matthes, Sigrun (author); Kern, Bastian (author); Dahlmann, K. (author); Frömming, C. (author) (2020)
A climate-optimized routing is expected as an operational measure to reduce the climate impact of aviation, whereas this routing causes extra aircraft operating costs. This study performs some air traffic simulations of nine aircraft routing strategies which include the climate-optimized routing, and examines characteristics of those routings. A total of 103 trans-Atlantic flights of an Airbus A330 is simulated for five weather types in winter and for three types in summer over the North Atlantic by using the chemistry-climate model EMAC with the air traffic simulation submodel AirTraf. For every weather type, the climate-optimized routing shows the minimum climate impact, whereas a trade-off exists between the costs and the climate impact. The cost-optimized routing lies between time- and fuel-optimized routings, and minimizes the costs. The aircraft routing for minimum contrail formation shows the second-lowest climate impact, whereas this routing also causes extra costs. Aircraft Noise and Climate Effects